Complementary Therapy Program of Ergonomic Exercise to Improve the Quality of Life of Elderly People with Hypertension - Didik Iman Margatot; Apridika Ajeng Kartika; Vania Ilmi Purwitasari (Jurnal Pengabdian Harapan Ibu (JPHI), 2026)
The increasing elderly population in Indonesia has resulted in a high prevalence of hypertension, which significantly reduces quality of life due to physical and psychological limitations. Safe and applicable non-pharmacological interventions are needed to support elderly blood pressure management. This community service activity aims to improve the quality of life of elderly people with hypertension in the Ngoresan Community Health Center (Puskesmas) working area through ergonomic exercise therapy training. The implementation method used a participatory approach that included health education, intensive training in six ergonomic exercise movements, and formative and summative evaluations in 43 elderly people. The results showed that most participants were able to perform the movements independently and correctly. Clinically, there was a significant decrease in average blood pressure from 150/90 mmHg to 140/80 mmHg in 70% of participants. In addition, there was an increase in understanding of hypertension management and motivation to perform exercise regularly. It was concluded that ergonomic exercise is effective as a complementary therapy in lowering blood pressure and improving fitness. This intervention is recommended to be integrated into a routine program at the elderly integrated health post (Posyandu) as a sustainable promotive and preventive effort.